Em busca de distinção e riquezas: patrimônios materiais e poder no sertão do rio Piranhas, Capitania da Parahyba Norte (segunda metade do séc. XVIII) - Silva, Janice Correa da (2013)
The main objective of this work is to undertake a historical research on material patrimonies in the sertão of Rio Piranhas, during the second half of the eighteenth century. Concerning the theoretical aspects the research was supported by the New Political History, and in this field, by the discussion of Political Culture concept. This work was also guided by other theoretical discussions, as it relates to patrimonialism, material culture and the Historical Culture. Thus, we intend to discuss the importance of judicial and notarial documents of Pombal municipality, in the sertão of Paraíba state, within the Political Culture of the Old Regime. We aim to understand how social actors sought to appropriate of the space (during the conquering process) and, therefore, the resources provided by nature, constituting their properties. An analysis of social relations in the sertão of Rio Piranhas, perceived as generating mechanisms that favored the accumulation of material goods and the consequent social rising became visible. The connections with other spaces, establishing friendly and conflict relations, constituting assets and wealth and managing them, is an appreciated aspect in this work. In order to unravel these problems, we used documental sources such as inventories and wills deposited in the Fórum Promotor Francisco Nelson da Nóbrega, in Pombal municipality, sertão of Paraiba. We also used powers of attorney found in the Cartório de 1º Ofício de Notas Coronel João Queiroga, in Pombal municipality. Requirements transcribed by João de Lyra Tavares and a few documental records from the Arquivo Histórico Ultramarino were used in our research as well.